Ierobežojumi un aizliegumi darba tiesiskajā regulējumā - Fridriksons, Henrihs (Latvijas Universitāte, 2011)
Darba tiesību jautājumi ir vieni no sarežģītākajiem un svarīgākajiem jautājumiem, ar kuriem saskaras cilvēki, jo gandrīz katrs cilvēks ir vai nu darbinieks vai darba devējs. Darba likumam piemīt mērķis darbinieku tiesiski aizsargāt no darba devēja puses. Tādēļ likumdevējs, izstrādājot un pieņemot Darba likumu, normās ir iestrādājis attīstīto pasaules valstu praksē vispāratzītos darba tiesību sistēmas pamatprincipus, kas jāievēro darba tiesiskajās attiecībās. Darba likuma normās ietvertie pamatprincipi kopumā atklāj darba tiesību īpatnības un būtību.

Title of bachelor's work is "Restrictions and Interdictions in the legal regulation of labor." In the first section the concept and an essence of the labour right, and as principles and restrictions according to principles is described. In the second section the concept of restriction and an interdiction of the labor law is described. In the third section subjects of legal relations and with them the connected interdictions and restrictions in the labor law are considered. Having studied the given sections, the author specifies in existing problems and additions to laws and as the author does conclusions and generalizations. Application of rules of law is very important legal action. Observance of legality, legal order, maintenance and protection of legal interests of workers depends on all-round, deep and well-founded application of rules of law.
Restrictions and Interdictions in the Labour Right
Keywords: Juridiskā zinātne